Celastrol induces apoptosis and autophagy via the ROS/JNK signaling pathway in human osteosarcoma cells: an in vitro and in vivo study - Li, H-Y (Cell Death Dis, 2015)
Osteosarcoma is the most common primary malignant tumor of bone, the long-term survival of which has stagnated in the past several decades. Celastrol, a triterpene from traditional Chinese medicine, has been proved to possess potent anti-tumor effect on various cancers. However, the effect of celastrol on human osteosarcoma and the underlying mechanisms remains to be elucidated. We reported here that celastrol could inhibit cell proliferation by causing G2/M phase arrest. Exposure to celastrol resulted in the activation of caspase-3, -8, and -9, indicating that celastrol induced apoptosis through both extrinsic and intrinsic pathways. Autophagy occurred in celastrol-treated cells as evidenced by formation of autophagosome and accumulation of LC3B-II. The celastrol-induced cell death was remarkably restored by the combination of autophagy and apoptosis inhibitors. Furthermore, inhibition of apoptosis enhanced autophagy while suppression of autophagy diminished apoptosis. Celastrol also induced JNK activation and ROS generation. The JNK inhibitor significantly attenuated celastrol-triggered apoptosis and autophagy while ROS scavenger could completely reverse them. The ROS scavenger also prevented G2/M phase arrest and phosphorylation of JNK. Importantly, we found that celastrol had the similar effects on primary osteosarcoma cells. Finally, in vivo, celastrol suppressed tumor growth in the mouse xenograft model. Taken together, our results revealed that celastrol caused G2/M phase arrest, induced apoptosis and autophagy via the ROS/JNK signaling pathway in human osteosarcoma cells. Celastrol is therefore a promising candidate for development of antitumor drugs targeting osteosarcoma.